Application of GC/MS-based metabonomic profiling in studying the lipid-regulating effects of Ginkgo biloba extract on diet-induced hyperlipidemia in rats - Zhang Qi; Wang Guang-ji; A Ji-ye; Wu Di; Zhu Ling-ling; Ma Bo; Du Yu (Acta Pharmacologica Sinica, 2016)
Aim: To evaluate the lipid-regulating effects of extract from Ginkgo biloba leaves (EGB) using pharmacological methods and metabonomic profiling in a rat model of diet-induced hyperlipidemia. Methods: EGB was orally administered at a dose level of 40 mg/kg in both the EGB-prevention and -treatment groups. All rat samples obtained were examined for known and potential biomarkers and enzyme activity using commercial assay kits and GC/MS-based metabonomic profiling coupled with principal component analysis (PCA). Results: The data obtained from the assay kits indicated that EGB reduced total cholesterol and low density lipoprotein cholesterol levels and increased high density lipoprotein cholesterol levels in rat plasma obtained from both the EGB-prevention and –treatment groups compared with those of the diet-induced hyperlipidemia group. EGB also increased the activities of lipoprotein lipase and hepatic lipase and excretion of fecal bile acid in rats from the EGB-prevention and–treatment groups. Using GC/MS-based metabonomic analysis, more than 40 endogenous metabolites were identified in rat plasma. PCA of rat plasma samples obtained using GC/MS produced a distinctive separation of the four treatment groups and sampling points within each group. Metabolic changes during hyperlipidemia formation and improvement resulting from EGB treatment were definitively monitored with PCA score plots. Furthermore, elevated levels of sorbitol, tyrosine, glutamine and glucose, and decreased levels of citric acid, galactose, palmitic acid, arachidonic acid, acetic acid, cholesterol, butyrate, creatinine, linoleate, ornithine and proline, were observed in the plasma of rats treated with EGB. Conclusion: EGB exerts multi-directional lipid-lowering effects on the rat metabonome, including limitation of the absorption of cholesterol, inactivation of HMGCoA and favorable regulation of profiles of essential polyunsaturated fatty acid (EFA). Further experiments are warranted to explore the mechanisms of action underlying the lipid-regulating effects of EGB against hyperlipidemia.